Reducing emissions of short-lived climate pollutants : perspectives on law and governance - Yamineva, Yulia; Kulovesi, Kati; Recio, Eugenia (International environmental law (Martinus Nijhoff) ;, 2024)
"Short-lived climate pollutants (SLCPs), including methane, black carbon, hydrofluorocarbons, and tropospheric ozone, have become part of climate policy debates. Discussion has revolved around the potential of their mitigation to slow down global warming in the short term and bring about co-benefits, for instance, for air quality and public health. This book provides the first comprehensive analysis of global SLCP law and governance. A diverse array of contributors delves into the science and evolution of the concept of SLCPs, analyses the legal and governance responses developed under various international and transnational arenas, and discusses selected sectoral case studies"--